Philippines : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency, Banking Supervision, Securities Regulation, Insurance Regulation, and Payment Systems. (IMF Staff Country Reports; Country Report ;, 2002)
This paper presents key findings of the Financial System Stability Assessment for the Philippines, including Reports on the Observance of Standards and Codes on Monetary and Financial Policy Transparency, Banking Supervision, Securities Regulation, Insurance Regulation, and Payment Systems. The Philippine financial system has undergone substantial reform in recent years, but faces significant vulnerabilities. The regulatory and supervisory framework has improved, and through mergers, price liberalization, and opening the system to foreign competition, the system is now more modern. However, distortions in the incentive framework currently constrain effective supervision and resolution.